Verification of Overhead Crane Simulator in a Training Centre - Dariusz KALWASIŃSKI (Problemy Mechatroniki)
This article presents the results from a practical test of a portable overhead crane simulator. The test was carried out to determine the usability of the simulator in the training being conducted. The simulator is developed using virtual reality (VR). With this solution, the user can be immersed in a virtual work environment.